If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (300 + -1x) * 100 = 110 Reorder the terms for easier multiplication: 100(300 + -1x) = 110 (300 * 100 + -1x * 100) = 110 (30000 + -100x) = 110 Solving 30000 + -100x = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30000' to each side of the equation. 30000 + -30000 + -100x = 110 + -30000 Combine like terms: 30000 + -30000 = 0 0 + -100x = 110 + -30000 -100x = 110 + -30000 Combine like terms: 110 + -30000 = -29890 -100x = -29890 Divide each side by '-100'. x = 298.9 Simplifying x = 298.9
| 4(3n+4)=2(6n+8) | | y-9x=22 | | 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x | | y=7500-9.5(8000) | | y=7500-9.5(10000) | | 25m=75 | | y=75000+9.5x | | 27+8=10 | | 4(C-9)C=15 | | 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 | | c-14=6 | | 6(10x-13)=222 | | -12/3x-41/7 |